2008
DOI: 10.1507/endocrj.k07-102
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Affects Osteopenia in Postmenopausal Patients with Primary Hyperparathyroidism

Abstract: Abstract. Controversy still exists about whether vitamin D status is related to the severity of primary hyperparathyroidism (pHPT), although vitamin D insufficiency is frequent in pHPT. The present study was therefore performed to examine the relationships between vitamin D status and various parameters in 30 postmenopausal pHPT patients. BMD values were measured by dual-energy x-ray absorptiometry at the lumbar spine (L 2-4 ), femoral neck (FN) and distal one third of the radius (Rad 1/3). Serum levels of 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Vitamin D-deficient PHPT patients have been reported to have higher PTH levels, greater adenoma weight, lower aBMD particularly at cortical sites, higher bone turnover, and increased fracture risk (1,2,(12)(13)(14)(15)(16)(17)(18)(19). Our disparate findings may be explained by the fact that these earlier studies were performed in settings (geographic or temporal) where long-standing, severe vitamin D deficiency and perhaps low calcium intake were commonplace.…”
Section: Discussionmentioning
confidence: 69%
“…Vitamin D-deficient PHPT patients have been reported to have higher PTH levels, greater adenoma weight, lower aBMD particularly at cortical sites, higher bone turnover, and increased fracture risk (1,2,(12)(13)(14)(15)(16)(17)(18)(19). Our disparate findings may be explained by the fact that these earlier studies were performed in settings (geographic or temporal) where long-standing, severe vitamin D deficiency and perhaps low calcium intake were commonplace.…”
Section: Discussionmentioning
confidence: 69%
“…The reason for the low levels of 25(OH)D and the correlation with PTH in the stone formers of our study is not clear; the complexity of PTH and vitamin D interactions, resulting in muscle and bone abnormalities in the general population [10,] have been related recently with the role of fibroblast growth factor 23 (FGF-23) and KLOTHO -regulators of phosphate excretion, PTH and calcitriol synthesis [11]. Reduced bone mass and high risk for osteoporotic fractures as a consequence of PTH and vitamin D abnormalities have also been documented in calcium stone formers [12,13,14,15], as well as a contributing role of FGF-23 and KLOTHO gene polymorphism in the pathogenesis of calcium nephrolithiasis [16,17].…”
Section: Discussionmentioning
confidence: 98%
“…The pathophysiological mechanisms responsible for the low serum 25(OH)D level in PHPT are not completely clarified. The data obtained from several studies suggest that vitamin D status might influence the clinical and biological expression of PHTP [1,2,[4][5][6][7][8][9][10][11][12][13][14][15] and even recovery after surgical treatment [11,16,17], although some authors have not found such an association [18,19].…”
Section: Introductionmentioning
confidence: 99%